Variations in some morphological characteristics of Polydora ciliata (Johnston) - Kendall, Michael A. (Journal of Natural History, 1980)
On investigation of a dense population of mud tube building polychaetes tentatively identified as Polydora ciliata it was found that many individuals also showed morphological characteristics more usually associated with other members of the same genus. This prompted the examination of the morphology of P. ciliata from a number of different areas with the aim of assessing the stability of some of the characters used in the taxonomy of its genus. These proved to be highly variable, did not group together consistently and overlapped with some of those of P. limicola (Annenkova) and P. ligni Webster. No clear distinction between P. ciliata and P. limicola could be made on the grounds of the characteristics examined but the overlap between P. ciliata and P. ligni was small.
World Polychaeta Database (WPolyDb)